The Community – Based Flood Disaster Risk Reduction (CBDRR) in Beringin Watershed in Semarang City - Tiara Sartika Worowirasmi; Miun Edi Waluyo; Yuliana Rachmawati; Itsna Yuni Hidayati (Jurnal Wilayah dan Lingkungan, 2015)
Limited land availability and weak regulation enforcement of land control trigger the land use change including the watershed area. Semarang City’s Spatial Plan 2011-2031 has determined Beringin as a buffer area with limited physical development allocation but the citizens utilized the watershed area for settlement. Settlement developments in the area reduce the watershed ability to catch water and river capacity due to increased sedimentation and become the main causes of the flash flood disaster (regularly in rainy season) in seven villages of Beringin watershed. This article is aimed to share the experiences in implementing the Beringin watershed of Community-Based Disaster Risk Reduction (CBDRR). The information was obtained by participatory mapping process, socialization of disaster awareness cultural understanding, focus group discussions, the formation of the Kelompok Siaga Bencana (KSB) and community groups, capacity building process of the KSB, table top exercise, emergency response simulation, and evacuation simulation. The results show that in 2012, Semarang City government developed Flood Forecasting and Warning System as one of Climate Change Adaptation Measures known as Flood Early Warning System (FEWS). One of the important outputs of the FEWS is community-based disaster risk reduction. Community participation process in the FEWS has made it possible for the community to identify disaster risk characteristics, to propose a solution for reducing flood risk which is suitable to the local wisdom, to increase the community capacity, and to organize one of themselves in a disaster preparedness group which run quite independently. It highlights that community in watershed needs a good solution to the flood problem due to their limitations to reduce the disaster risk.